Invasion of water hyacinth and water lettuce inhibits the abundance of epiphytic algae. (31st March 2022) - Lv, Tian; Fan, Shufeng; Wang, Huiyuan; Li, Dexiang; Wang, Qiuyue; Lei, Xinyi; Liu, Chunhua; Yu, Dan
Abstract: Aim: The invasion of exotic macrophytes causes native biodiversity loss in aquatic ecosystems of China. However, the influence of invasive free‐floating macrophytes on epiphytic algal communities has rarely been reported, especially in comparison with those of native free‐floating macrophytes. Region: Southern China. Methods: We investigated the interrelationship between epiphytic algal communities on the roots of three free‐floating macrophytes [two invasive species ( Eichhornia crassipes and Pistia stratiotes ) and one native species ( Hydrocharis dubia )] and environmental factors in 40 natural freshwater ecosystems throughout southern China. We also tested the relationship between allelochemicals from the macrophytes and epiphytic algae. A mesocosm experiment was conducted to verify the discoveries of the field investigation. Results: The abundance of epiphytic algae on the invasive macrophytes was lower than that on the native species in the field investigation and mesocosm experiment. Macrophyte traits were the main factor explaining the epiphytic algal abundance in both the field investigation and mesocosm experiment. In linear models, the slopes of epiphytic algal abundance were lower across gradients of native macrophyte biomass and coverage than across gradients of invasive macrophyte biomass and coverage. The allelochemical contents secreted by the invasive macrophytes were significantly higher than those secreted by the native species. The composition of allelochemicals was another factor that drove the decrease in epiphytic algal abundance. Among the allelochemicals, organic acids and alkaloids were abundant. Main Conclusions: The inhibitory effect of two invasive free‐floating macrophytes on epiphytic algae is stronger than that of the native macrophyte H . dubia . The main reason for this finding is that the invasive macrophytes have greater biomass and occupied more space, resulting in greater limitations on spatial niches and resources. Moreover, invasive macrophytes release more allelochemicals than native macrophytes, leading to stronger inhibitory effects on epiphytic algae.